2021
DOI: 10.2147/cmar.s287128
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific PET Radiomic Prediction Model for the Histological Subtype Classification of Non-Small-Cell Lung Cancer

Abstract: Purpose: To investigate the impact of staging on differences in glucose metabolic heterogeneity between lung adenocarcinoma (ADC) and squamous cell carcinoma (SCC) by 18 F-fluorodeoxyglucose positron emission tomography (18 F-FDG PET) textural analysis and to develop a stage-specific PET radiomic prediction model to distinguish lung ADC from SCC. Patients and Methods: Patients who were histologically diagnosed with lung ADC or SCC and underwent pretreatment 18 F-FDG PET/CT scans were retrospectively identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although radiomics has not been widely used in the clinic, many studies have shown its excellent performance in tumor diagnosis and efficacy prediction. 49 , 50 As multidisciplinary overlap is an inexorable trend in modern medicine, we expect the widespread adoption of a standardized radiomic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiomics has not been widely used in the clinic, many studies have shown its excellent performance in tumor diagnosis and efficacy prediction. 49 , 50 As multidisciplinary overlap is an inexorable trend in modern medicine, we expect the widespread adoption of a standardized radiomic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…To make the model developed more predictive and robust, feature selection is a crucial step of a radiomics study ( 27 ). The Rad-Score consisted of eight features, and nearly all of the selected predictive features were wavelet, similar to the results of several published studies ( 28 - 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the two different types of lung cancer have different prognoses, an accurate pre-operative diagnosis will lead to appropriate treatment and will improve patient prognosis. Several studies have shown that radiomic analysis could help to classify the histological lung cancer subtypes shown in Table 3 [21,[65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Lu et al reported that radiomics models yielded the diagnostic performance (AUC) of 0.741 (SCLC vs. NSCLC), 0.822 (AD vs. SCLC), 0.665 (SCC vs. SCLC), and 0.655 (AD vs. SCC) in the classification of histopathologic lung cancer subtypes [71].…”
Section: Application In Classifying Histological Subtypes Of Early Lu...mentioning
confidence: 99%
“…Therefore, it is necessary to cross-validate data using multi-center cohort data in the future. [70] 349 CT SPN Yes (internal) No Accuracy = 89% Yan lei Ji [72] 253 CT SPN Yes (internal) Yes AUC = 0.982 (ADC vs. SCC) Jianyuan ZHOU [78] 182 PET-CT SPN Yes (internal) Yes AUC = 0.862 (Sensitivity = 88%, Specificity = 72.73%, ADC vs. SCC) Xue Sha [69] 100 PET-CT SPN Yes (internal) Yes AUC = 0.781 (Sensitivity = 100%, Specificity = 70%, ADC vs. SCC) Weimiao Wu [66] 350 CT SPN Yes (internal) Yes AUC = 0.72 (ADC vs. SCC) ADC: adenocarcinoma; SCLC: small cell lung cancer; NSCLC: non-small cell lung cancer; SCC: squamous cell carcinoma. a Group: refers to the type of lung nodules analyzed in this study.…”
Section: Application In Classifying Histological Subtypes Of Early Lu...mentioning
confidence: 99%